FAKTOR-FAKTOR PENENTU KEPUTUSAN INVESTOR UNTUK MEMBIAYAI INFRASTRUKTUR PUBLIK DI INDONESIA MELALUI KEMITRAAN PEMERINTAH DAN SWASTA - Amin, Ahmad; Perdana, Halim Dedy; Ekanindya, Ria (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2025)
This study examines the factors that influence investors' intention to finance public infrastructure in Indonesia through the Public Private Partnership (PPP) scheme. Different from previous studies conducted by Hamami et al. (2006), Banerjee et al. (2006), Side and Mendoza (2010), and Sharma (2012) focusing on financial aspects, this study emphasizes non-financial factors, particularly trust in government as a direct influence on investment intention. In addition, this study also examines the effect of government service quality, government transparency, and value similarity on investment intentions with trust in government as a mediating variable. Grounded in institutional theory, stakeholder theory, and stewardship theory, this study highlights the role of government legitimacy and good governance in encouraging private sector participation in infrastructure provision. Data was collected through a survey of 165 executives of companies listed on the Indonesia Stock Exchange (IDX) and analyzed using SEM-PLS. The results show that service quality, transparency, and value similarity positively affect trust in government, which in turn increases investment intentions. However, value institutionalization as a moderating variable showed no significant effect. This study confirms that investment intentions depend not only on financial factors, but also on trust built through good governance and the adoption of shared values between the government and the private sector.